Powidoki twórczości Federica Felliniego w "Mieście Snu" Krystiana Lupy - Gołos-Dąbrowska, Katarzyna (Załącznik Kulturoznawczy, 2023)
Afterimages of Federico Fellini’s Works in Krystian Lupa’s The City of Dream The main purpose of this article is to analyze Krystian Lupa’s production The City of Dream (TR Warsaw, 2012), based on the novel The Other Side by Alfred Kubin, relative to the work of Federico Fellini. The Polish director, who very often refers to the medium of film in his theatre productions, this time turned to the work of Federico Fellini. One of the themes of the play is the process of making a fictional documentary film by the Italian director. Lupa refers to Fellini’s work by stylizing some scenes from his films. He “borrows” characters from the filmmaker’s motion pictures and the Italian’s biography. He also adapts scenes from Fellini’s feature films and commercials. The purpose of the text is to highlight, analyze, and interpret the intertextual references found in the play.